Determining the Effects of Central-Peripheral interactions on the Distribution of Human Activity in Space - António Rodrigues (European Regional Science Association (ERSA), 2011)
Natural advantages determine where agglomerations emerge. Also, efficiency and economies of scale determine how many agglomerations subsist and how they interact, forming complex urban hierarquies. Moreover, physical characteristics influence the way humans divide land into irregular parcels we call administrative regions. If, on one hand, initial location advantages are responsible for defining where the main urban nodes will grow and subsist because of lock-in effects, central-peripheral relations play a decisive role in defining the distribution of activity in space. This paper explores the importance of location in relation to the main centripetal nodes. A central-peripheral model, taking into account spatial heterogeneity patterns, explains how activity is organized in Continental Portugal. A bayesian framework will allow the comparison of posterior densities for distinct parts of the country.
Keywords: 330